Tempol Ameliorates and Prevents Mechanical Hyperalgesia in a Rat Model of Chemotherapy-Induced Neuropathic Pain - Kim, Hee Kee; Hwang, Seon-Hee; Abdi, Salahadin (Frontiers in Pharmacology, 2017)
Chemotherapy-induced neuropathic pain is difficult to treat and prevent. Tempol decreases cellular superoxide radical levels and oxidative stress. The aims of our study were to investigate the analgesic and preventive effects of tempol on paclitaxel-induced neuropathic pain in rats and to identify the associated mechanisms of action. Neuropathic pain was induced with intraperitoneally injected paclitaxel on four alternate days in male Sprague-Dawley rats. Tempol was administered systemically as a single injection and a continuous infusion before or after the injection of paclitaxel. The mechanical threshold for allodynia, protein levels, and free radical levels were measured using von Frey filaments, Western blotting, and live cell imaging, respectively. After the rats developed neuropathic pain behavior, a single intraperitoneal injection and continuous infusion of tempol ameliorated paclitaxel-induced mechanical allodynia. Systemic infusion of tempol in the early phase of the development of pain behavior prevented the development of paclitaxel-induced pain behavior. Paclitaxel increased the levels of phosphorylated protein kinase C (p-PKC), phosphorylated nuclear factor κB (p-NF-κB), phosphodiesterase 4D (PDE4D), IL-1β, and monocyte chemoattractant protein-1 (MCP-1) in the lumbar dorsal root ganglia; however, tempol decreased these levels. Paclitaxel also increased superoxide levels in a culture of primary dorsal root ganglion cells and tempol decreased these levels. In conclusion, tempol alleviates and prevents chemotherapy-induced neuropathic pain in rats by reducing the levels of inflammatory cytokines and free radicals in dorsal root ganglia.